The Relationship Between Nurses' Performance in Carrying out Nursing Care and the Quality of Nursing Services in Hospitals - Alamsyah; Tut Handayani; Lestyani; Iismayanti (CV. Get Press Indonesia, 2024)
Health care is a fundamental aspect of the health system that directly affects people's quality of life (Feoh & Barimbing, 2022). Hospitals as one of the main health care facilities have a crucial role in providing high-quality medical and nursing care (Nasution, 2020). This study aims to identify and analyse the relationship between nurses' performance in implementing nursing care and the quality of nursing services in hospitals. This study used a cross-sectional research design, which aims to evaluate the relationship between nurses' performance in carrying out nursing care and the quality of nursing services in the hospital at one specific point in time. Table 1 shows the frequency distribution of nurses' performance in performing nursing care. Of the total 62 nurses sampled, 27 nurses (43.5%) were categorised as having poor performance, while 35 nurses (56.5%) were categorised as having good performance. Table 2 shows the frequency distribution of nursing service quality. Of the total 62 respondents, 29 (46.8%) were dissatisfied with the quality of care provided, while 33 (53.2%) were satisfied. The results demonstrated that 17 patients (27.4%) who received care from nurses with poor performance levels expressed dissatisfaction, while 10 patients (16.1%) were satisfied with the services provided. Conversely, among nurses with good performance, 12 patients (19.4%) were dissatisfied, while 23 patients (37.1%) expressed satisfaction with the services received. The implementation of continuous training and regular evaluation of nurses' performance can be a strategic step to achieve this goal.